Analisis Kelayakan Usaha Batu Bata (Studi Kasus: Desa Tanjung Mulia Kecamatan Pagar Merbau) - Muhammad Arasy; Khairul Saleh; Rahma Sari Siregar (Universitas Medan Area, 2021)
This study aims to determine the feasibility of the business whether the brick business is feasible to run, the brick-making business using clay and red earth as raw material with diesel fuel for dompleng machines and oil palm bunches and firewood as fuel, knowing the amount of income. , knowing the level of business feasibility in the village of Tanjung Mulia. This research was conducted from October 2020. The determination of the research location was determined purposively because considering the time and reach of the researchers, a sample of 62 brick craftsmen were determined by the census method, the data used were primary data and secondary data. The research method used to determine the availability of inputs (raw materials, capital, labor) and to determine income using income analysis, to analyze business feasibility using the R / C ratio and BEP. The results of the study show that inputs (raw materials, capital, labor) are sufficiently available in the research area. The income from the brick making business is Rp. 18,769,903, - / month. Obtained Net Revenew Cost Ratio (Net R / C Ratio) the value of R / C Ratio is greater than one (R / C 1 or 1.18 1), Break Even Point (BEP) the break even point of the price is at Rp. 310 / pieces of bricks and the breakeven point of production is at 349,998 pieces / month. Based on these results, the brick business in Tanjung Mulia Village, Pagar Merbau District is feasible to run.